Cardiovascular-metabolic responses and oxygen uptake kinetics during kayak paddling in normobaric hypoxia in young flatwater kayakers - Onarici Gungor, E.; Kacoglu, C.; Cerrah, A. O.; Yilmaz, I. (Baltic Journal of Health and Physical Activity, 2021)
Background: The aim of the study was to evaluate response of cardiovascular, metabolic and oxygen consumption kinetics at kayak paddling exercise in the normoxic and normobaric environment. Material and Methods: Seven kayakers (age: 16±1.2 year; height: 165±8.3cm; body weight: 53±8kg; fat percentage: 17±4.4%; VO2max: 34.57±9.24 ml.kg-1.dk-1; Maximal La: 8.72±2.75 mM) with four years` experience participated in the study. All subjects performed incremental maximal and sub-threshold constant load kayak paddling tests in normoxic and normobaric hypoxic conditions on different days. According to maximal tests results, the individual anaerobic threshold and VO2max values were determined. Results: VO2max, HRmax, peak power and maximal lactate values demonstrated statistical significant differences between the normobaric hypoxia and normoxic environment. The response of VO2max was found higher in the normoxic than the normobaric environment. Oxygen uptake kinetic was statistically (p<0.05) faster, and O2 values were lower (p<0.05) in the normoxic than the normobaric environment. Recovery kinetics was found to be statistically faster (p<0.05) in the hypoxia than in the normoxia environment. Conclusions: The ATP supply in an anaerobic way was higher in the normoxic environment than in the normobaric environment, and lactate tolerance increased. Having faster oxygen uptake kinetics in the normoxic environment shows that the volume of oxygen deficit is lower. Faster recovery kinetics in normobaric hypoxia shows the positive effects of altitude on recovery.